Health-Seeking Behavior among Tuberculosis Suspected Cases in Major Cities of Mongolia - Ochirdorj, Gerelmaa; Boldoo, Tsolmon; Dambaa, Naranzul; Sovd, Tugsdelger; Ichimura, Yasunori; Nyamadawa, Naranbat; Ganbat, Mandukhai; Dambadarjaa, Davaalkham (Central Asian Journal of Medical Sciences, 2019)
Objective: To assess the health-seeking behavior among presumptive TB cases in a Mongolian population-based TB prevalence survey. Tuberculosis (TB) is a major public health concern in Mongolia. TB prevalence survey provides a chance to explore health seeking behavior at the population level. Methods: A population based, cross-sectional survey was conducted using 51 cluster samplings in Mongolia. Participants were interviewed for TB symptoms and their health seeking behavior aged 15 years and above. Participants with a cough lasting two weeks were classified as TB suspects. Results: Of 27,112 survey participants, 4.6% had cough more than two weeks. Forty-eight percent of them had sought health care and to reported pharmacies (26.2%), family group practitioners (45.7%), district health centers (13.3%), and private physicians (3.6%) as first point of contact. The young adults (46.8%) and students (61.0%) approached pharmacies for care more often than their counterparts. Preference for family clinics increased with age. Conclusions: In this survey, 48.1% of the TB suspects had visited a health-care provider. TB case detection need to be improved by retraining health staffs of family health facilities.